An Image Fusion Method Based On Framelet Transform - Patel Kalpana Dhanji; Santhosh Kumar Singh (Institute of Advanced Engineering and Science, 2018)
Image fusion is the process of combining relevant information from two or more images into a single image. The resulting image contains more information as compared to individual images. In this system, we are proposing a new image fusion method by using a technique called framelet transform. This method consists of two phases; First is the frame separation where the pre-processing and Selection of frames for both the images occurs and the second phase is the Frame fusion that is done by inverse framelet transform method is done from which a fused output images will be formed that will be containing both the information of the input images (CT & MRI images).